The Discovery of GALM Deficiency (Type IV Galactosemia) and Newborn Screening System for Galactosemia in Japan - Atsuo Kikuchi; Yoichi Wada; Toshihiro Ohura; Shigeo Kure (MDPI AG, 2021)
The Leloir pathway, which consists of highly conserved enzymes, metabolizes galactose. Deficits in three enzymes in this pathway, namely galactose-1-phosphate uridylyltransferase (GALT), galactokinase (GALK1), and UDP-galactose-4'-epimerase (GALE), are associated with genetic galactosemia. We recently identified patients with galactosemia and biallelic variants in GALM, encoding galactose epimerase (GALM), an enzyme that is directly upstream of GALK1. GALM deficiency was subsequently designated as type IV galactosemia. Currently, all the published patients with biallelic GALM variants were found through newborn screening in Japan. Here, we review GALM deficiency and describe how we discovered this relatively mild but not rare disease through the newborn screening system in Japan.